Successful Management of Necrotizing Fasciitis of Perianal Region due to Kobiraji Maltreatment for Hemorrhoids - Hanif, Md; Tasnim, Masuma; Hamid, Abdul; Islam, Sardar Mohammad Rezaul (Journal of Armed Forces Medical College, Bangladesh, 2024)
Necrotizing fasciitis (NF), an invasive soft-tissue infection that affects the fascia superficially and spreads quickly along subcutaneous tissue. It is a medical- surgical emergency. The patient may have symptoms that are not consistent with the clinical findings, such as a temperature, evidence of local inflammation, and acute pain. Patients typically present at a later stage, but because there are few cutaneous signs in the early stages, diagnosis might be difficult. Thus, a high index of suspicion plays a crucial role in the NF diagnosis. Furthermore, intraoperative diagnosis frequently serves as a confirmation. The cornerstones of the treatment include analgesia, hydration and electrolyte control, intravenous antibiotics and prompt surgical debridement. JAFMC Bangladesh, Vol 19, No 2 (December) 2023: 42-46